Docosahexaenoic acid lowers phosphatidate level in human activated lymphocytes despite phospholipase D activation - Shaliha Bechoua; Madeleine Dubois; Georges Némoz; Michel Lagarde; Annie-France Prigent (Journal of Lipid Research, 1998)
N–3 polyunsaturated fatty acids from marine oil have been shown to decrease T cell-mediated immune function both in animals and humans, and to inhibit the mitogen-induced lymphoproliferative response when added to lymphocyte culture medium. As phosphatidic acid (PA) is a key mediator of the mitogenic process, the present study aims to investigate whether docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids, the main n–3 fatty acids from fish oil, are able to alter the mitogen-induced synthesis of PA, when added to the culture medium of human peripheral blood mononuclear cells (PBMC). Incubation of PBMC in a medium containing 5 μM DHA bound to 5 μM human delipidated serum albumin induced a 2–fold increase in the basal PA mass whereas incubation with EPA, in the same conditions, had no effect. In contrast, both fatty acids markedly reduced the concanavalin A (ConA)-induced production of PA as compared with untreated cells. Paradoxically, phospholipase D (PLD) activity, evidenced by the synthesis of phosphatidylbutanol, was only detected in DHA-treated cells further stimulated by ConA, indicating that both DHA and ConA are required for PLD activation. Similarly, an increased diacylglycerol (DAG) mass was only observed in DHA-treated cells stimulated by ConA, whereas no modification occurred in control or EPA-treated cells stimulated or not by ConA. Furthermore, 1-butanol suppressed the ConA-induced increase of DAG mass observed in DHA-treated cells, indicating that phosphatidate was the source of the newly synthesized diacylglycerol. Altogether, these results show that, in concanavalin A-activated human peripheral blood mononuclear cells, docosahexaenoate stimulates both phospholipase D and phosphatidate phosphohydrolase activities, which ultimately results in an increased diacylglycerol production at the expense of phosphatidate.—Bechoua, S., M. Dubois, G. Némoz, M. Lagarde, and A-F. Prigent. Docasahexaenoic acid lowers phosphatidate level in human activated lymphocytes despite phospholipase D activation. J. Lipid Res. 1998. 39: 873–883.